EXPLORING THE POTENTIAL OF ONLINE GROUP COUNSELING : A CASE-STUDY FOR MAURITIAN STUDENTS PRESENTING THE INTERNET ADDICTION DISORDER SYNDROME - Harry, Ponnusawmy; Issack, Santally Mohammad (European Scientific Journal, ESJ, 2014)
Investigating the prevalence of Internet addiction disorder among Mauritian students at tertiary level seems to be appropriate, especially at a time when Internet access cost is becoming cheaper and number of user is, consequently, growing. This research, structured with an initial preliminary investigation about online behaviors of tertiary students and the psychological features associated with Internet addiction, explores the design and implementation of online counseling. A random sample of more than eighty participants completed a web-based questionnaire, which was used to assess the usage, influence and depth of penetration of Internet in students’ life at the University of Mauritius. Backup with a critical literature review, this research study used a methodological framework to setup online counseling session for treating Internet Addiction disorder (IAD). The design and implementation process was developed and analyzed after a group of nine counsellees completed online group counseling sessions for IAD, by extensive use of discussion forum for communication purpose. The three months long program ended with a feedback questionnaire, where participants responded to a series of open and closed-ended type questions pertaining to whether they found the counseling sessions to be helpful, useful and meaningful. Moreover, the best features of the online platform and areas which needs improvement were also queried. From a compilation of advantages of using a virtual environment, bbenefits of online counseling were deduced and the whole implementation process was presented as a model which can be used to screen counselee for online counseling program to handle IAD and provide remedial solutions via a computer-mediated platform, if needed.